Analisa Distibusi Fragmentasi Pada Kegiatan Peledakan Batuan Dengan Menggunakan Simulasi Monte Carlo - Dedi Yulhendra; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2018)
This Research based on the partially fragmentation which the boulders blasting results more than 80cms that intervene the crusher’s performance. The purpose of this Final Project is to get the exact value of powder factor; in order to attain the value of fragmentation up to 80 with optimally hold on 10%.The methodology problem that used is finding the value of rock factor by using Monte Carlo simulation and calculate the effect of powder factor on fragmentation with linear regression.The result of this final project is attained the value of rock factor 5.01 by using Monte Carlo simulation and the relationship between powder factor with the fragmentation is 72% with equation Y = -102,89X + 50,086. Based on its calculation, to attain the maximum result of fragmentation holding up to 10%, therefore the exact value of powder factor is 0,389.  Keywords: boulder, fragmentation, powder factor, rock factor